Healthcare Access among Older Rural Women Veterans in Utah*. (17th September 2020) - Ward, Carol J.; Cope, Michael R.; Jackson, Jorden
Abstract: Using gender and life course frameworks attuned to overlapping roles and statuses, this exploratory case study highlights the experiences of older, rural female veterans in Utah with accessing Veterans Administration and other healthcare. Based on three focus groups with 22 women, findings show that these veterans experienced similar healthcare access obstacles to female veterans in other contexts. Most also experienced invisibility and discrimination in the military, which carried over as they became veterans. However, while these older, rural women veterans voiced new concerns about their own healthcare in later life course stages, they also described extensive experience with coordination of services and advocacy for other veterans, family and rural community members. Thus, these women veterans acted as healthcare advocates in a complex, bureaucratic, strained system. Feeling largely excluded from the male veterans' networks and organizations, they perceived the need to create new networks that could assist veterans in need.